Influence of different durations of estrogen deficiency on alveolar bone loss in rats - Susana Ungaro Amadei; Daniela Martins de Souza; Adriana Aigotti Haberbeck Brandão; Rosilene Fernandes da Rocha (Sociedade Brasileira de Pesquisa Odontológica, 2011)
The purpose of this study was to morphometrically evaluate the influence of different durations of ovariectomy-induced estrogen deficiency on alveolar bone loss associated with ligature-induced bone loss in rats. Sixty female Wistar rats were randomly assigned to ovariectomy (OVX test group) or sham operation (SHAM control group). The OVX and SHAM groups were each distributed into three subgroups of ten rats each according to the duration of estrogen deficiency (30, 60 and 90 postoperative days). In all groups, for the last 30 days of the experimental period, cotton ligatures were placed around the cervix of the right upper second molar; the contralateral tooth was left unligated to serve as a control. The maxillary bones were removed, and the alveolar bone loss was analyzed by measuring the distance between the cementoenamel junction and the alveolar bone crest at the buccal site of the right upper second molar. A comparison between the ligated and unligated groups verified the presence of ligature-induced alveolar bone loss (p < 0.05). No significant differences were observed among the unligated groups (p > 0.05). A significant increase in bone loss was observed when ligation occurred 90 days after ovariectomy compared with the sham group (p < 0.05). These results demonstrate that long-term estrogen deficiency affects ligature-induced alveolar bone loss.